Weighing the role of self-regulation and self-concept on job search anxiety among Higher Education Graduates - Nurramadhani, Athifah; Fatuhrahmah, Ufi (Universitas Ahmad Dahlan, 2023)
Job search anxiety in Indonesia has increased during and after the pandemic due to the ongoing economic and business situation. Internal factors are considered to be key influencers affecting this anxiety, including self-regulation and self-concept. This research aims to explore the relationship between self-regulation, self-concept, and job search anxiety among higher education graduates. The study involved 200 participants characterized by a minimum of a D3 education level, graduated between 2021-2022, and currently in the process of their first job search. Employing a quantitative approach, the research utilized three scales: self-regulation scale, self-concept scale, and job search anxiety scale, analyzed using multiple linear regression analysis. The results indicate that self-regulation and self-concept simultaneously contribute to job search anxiety. This study suggests the importance of simultaneously strengthening self-concept and self-regulation in preparing graduating students to minimize arising levels of anxiety, ultimately aiding them in achieving their desired career and job objectives.